Strategic Determinants of Economic Complexity in Türkiye: Knowledge, Technology, and Institutions - Acaravci, Ali; Baş, Gizem; Kakilli Acaravci, Songül; Hallumoğlu, Çilem Eda (International Review of Management and Marketing, 2026)
This study examines the strategic determinants of economic complexity in Türkiye by exploring the roles of institutional quality, knowledge management, technology transfer, and foreign direct investment (FDI) in shaping national productive capabilities. The analysis uses annual data for the period 1996–2023. Economic complexity is measured by the Economic Complexity Index, while institutional quality, capital goods imports, research and development (R&D) expenditures. The Fourier Bootstrap Autoregressive Distributed Lag (FBARDL) approach is employed to examine long-run relationships while accounting for structural breaks and the relatively small sample size. The empirical findings reveal a stable long-run relationship among the variables. Institutional quality, capital goods imports, and R&D expenditures positively affect economic complexity, indicating that effective governance, technological acquisition, and domestic knowledge creation play important roles in strengthening productive capabilities. In contrast, FDI has a negative long-run effect, suggesting that foreign investment alone may not generate capability upgrading and can reinforce dependency when domestic absorptive capacity and local linkages remain weak. This study provides a more comprehensive understanding of productive capabilities by connecting Economic Complexity Theory with Strategic Management and International Business. The findings indicate that emerging economies need strong domestic capabilities and effective use of external knowledge to improve competitiveness and economic complexity.